Extracellular matrix remodelling in response to venous hypertension: proteomics of human varicose veins. Issue 3 (11th April 2016) - Barallobre-Barreiro, Javier; Oklu, Rahmi; Lynch, Marc; Fava, Marika; Baig, Ferheen; Yin, Xiaoke; Barwari, Temo; Potier, David N.; Albadawi, Hassan; Jahangiri, Marjan; Porter, Karen E.; Watkins, Michael T.; et al.
Abstract: Aims: Extracellular matrix remodelling has been implicated in a number of vascular conditions, including venous hypertension and varicose veins. However, to date, no systematic analysis of matrix remodelling in human veins has been performed. Methods and results: To understand the consequences of venous hypertension, normal and varicose veins were evaluated using proteomics approaches targeting the extracellular matrix. Varicose saphenous veins removed during phlebectomy and normal saphenous veins obtained during coronary artery bypass surgery were collected for proteomics analysis. Extracellular matrix proteins were enriched from venous tissues. The proteomics analysis revealed the presence of >150 extracellular matrix proteins, of which 48 had not been previously detected in venous tissue. Extracellular matrix remodelling in varicose veins was characterized by a loss of aggrecan and several small leucine-rich proteoglycans and a compensatory increase in collagen I and laminins. Gene expression analysis of the same tissues suggested that the remodelling process associated with venous hypertension predominantly occurs at the protein rather than the transcript level. The loss of aggrecan in varicose veins was paralleled by a reduced expression of aggrecanases. Chymase and tryptase β1 were among the up-regulated proteases. The effect of these serine proteases on the venous extracellular matrix was further explored by incubating normal saphenous veins with recombinant enzymes. Proteomics analysis revealed extensive extracellular matrix degradation after digestion with tryptase β1. In comparison, chymase was less potent and degraded predominantly basement membrane-associated proteins. Conclusion: The present proteomics study provides unprecedented insights into the expression and degradation of structural and regulatory components of the vascular extracellular matrix in varicosis.